2023
DOI: 10.3390/nu15081880
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic and Probiotic Modulation of the Microbiota–Gut–Brain Axis in Depression

Abstract: Emerging evidence demonstrates that alterations to the gut microbiota can affect mood, suggesting that the microbiota–gut–brain (MGB) axis contributes to the pathogenesis of depression. Many of these pathways overlap with the way in which the gut microbiota are thought to contribute to metabolic disease progression and obesity. In rodents, prebiotics and probiotics have been shown to modulate the composition and function of the gut microbiota. Together with germ-free rodent models, probiotics have provided com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 174 publications
0
8
0
Order By: Relevance
“…C. C. Kao et al, 2016; A. C.-C. Kao, Burnet, et al, 2018; Radford-Smith & Anthony, 2023). Following this, the present investigation lays the groundwork for clinical trials to determine whether the findings observed in rodents correlate with the effects of lurasidone on the human gut microbiome.…”
Section: Discussionmentioning
confidence: 98%
“…C. C. Kao et al, 2016; A. C.-C. Kao, Burnet, et al, 2018; Radford-Smith & Anthony, 2023). Following this, the present investigation lays the groundwork for clinical trials to determine whether the findings observed in rodents correlate with the effects of lurasidone on the human gut microbiome.…”
Section: Discussionmentioning
confidence: 98%
“…Recent research has explored the effects of various prebiotic fibers, such as inulin, fructooligosaccharides, and galactooligosaccharides, on the BGM system. 119 , 120 Several studies have shown that prebiotic supplementation can modulate the gut microbial composition positively, increase the production of SCFAs, and improve gut barrier function. 121 These effects have been associated with improved cognitive function, reduced anxiety-like behavior, and enhanced stress resilience in animal models, but clinically meaningful effects need to be confirmed in well-controlled human studies.…”
Section: Modulation Of the Bgm Systemmentioning
confidence: 99%
“…For example, bacterial fermentation products such as SCFAs have been linked to the pathogenesis of depression (Radford‐Smith & Anthony, 2023). However, there is an overlap between the proposed pathways of cognitive disfunction caused by bacteria and the way in which the gut microbiota is considered to contribute to metabolic disease progression and obesity (Radford‐Smith & Anthony, 2023). Additionally, cognitive impairment has been previously linked to inflammation as well as to barrier disruption in both the gut and brain (Leigh & Morris, 2020).…”
Section: Beneficial Neurocognitive Effects Of Hmosmentioning
confidence: 99%
“…The bacterial composition of the GI tract has been linked to changes in the brain and behavior, particularly with respect to cognitive function (Gareau, 2016). For example, bacterial fermentation products such as SCFAs have been linked to the pathogenesis of depression (Radford‐Smith & Anthony, 2023). However, there is an overlap between the proposed pathways of cognitive disfunction caused by bacteria and the way in which the gut microbiota is considered to contribute to metabolic disease progression and obesity (Radford‐Smith & Anthony, 2023).…”
Section: Beneficial Neurocognitive Effects Of Hmosmentioning
confidence: 99%